Spectral and dynamical study of III–V triple junction solar cells and the application to multiflash I–V measurement - Socolovsky, Hernán Pablo (2015)
Fil: Socolovsky, Hernán Pablo. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina